Исследования археологического комплекса Маяки в среднем течении Северского Донца в 2008 г. - Кравченко, Э.Е.; Петренко, А.Н. (Археологічні дослідження в Україні, 2009)
In 2008, the research of archaeological complex near Maya ky village in the area of middle flow of the Siverskyi Donets River was ongoing. Two trenches were laid at the site, one of which (31) was situated at «posad» (trading quarter) and another (32) at the settlement. The remains of the structures of the Early Iron Age, the Khozars and the Golden Horde times were discovered.